2022
DOI: 10.3389/fendo.2022.843573
|View full text |Cite
|
Sign up to set email alerts
|

The Application Value of the Central Lymph Node Metastasis Risk Assessment Model in Papillary Thyroid Microcarcinoma of Stage cN0: A Study of 828 Patients

Abstract: BackgroundThe aim of this study is to build a risk assessment system for central lymph node metastasis (CLNM) in papillary thyroid microcarcinoma (PTMC) of stage cN0 and to explore its application value in clinical practice.MethodsA total of 500 patients with PTMC who underwent thyroid operation from 2013 to 2015 in Ningbo First Hospital were selected as the model group. Independent risk factors related to CLNM in PTMC were analyzed and determined, and a risk assessment system for CLNM was preliminarily establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…According to the lymphatic drainage pathway, LNM typically occurs initially in the central compartment before involving the lateral compartment, sometimes presenting as skip metastasis [ 6 , 7 ]. The incidence of CLNM in PTC patients is high, ranging from 21 to 60% [ 8 , 9 ], and approximately 20% of PTC cases are accompanied by LLNM at the initial diagnosis [ 10 , 11 ]. Considerable studies have shown that LLNM might increase the risk of local recurrence and reduce the survival rate [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the lymphatic drainage pathway, LNM typically occurs initially in the central compartment before involving the lateral compartment, sometimes presenting as skip metastasis [ 6 , 7 ]. The incidence of CLNM in PTC patients is high, ranging from 21 to 60% [ 8 , 9 ], and approximately 20% of PTC cases are accompanied by LLNM at the initial diagnosis [ 10 , 11 ]. Considerable studies have shown that LLNM might increase the risk of local recurrence and reduce the survival rate [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the models established in many studies have used the classi cation results of thyroid aspiration cytology or capsular invasion as predictors. 16,38,39 These predictors are directly related to the pathological status of thyroid cancer and are not used for early screening purposes. A real-world study conducted in China con rmed that the sensitivity of preoperative diagnosis of CLNM by ultrasound alone is very limited.…”
Section: Ghai Et Al Previously Summarized the Factors Affecting Tirad...mentioning
confidence: 99%